Financial Performance among Selected Liquified Petroleum Gas (LPG) Retail Stores in Talisay City, Cebu - Romero, Charlotte; Polinar, Mark Anthony N.; Delantar, Alexander Franco A. (Future Science / FSH-PH Publications, 2024)
The Liquified Petroleum Gas (LPG) sector plays a noteworthy part in the local economy, supplying essential energy resources for residential and commercial use. The COVID-19 pandemic has brought massive distractions that significantly affect the financial performance of companies, regardless of the sector they belong to, and this sector is not exempted. This study examined the financial performance of these LPG retail stores in Talisay City, Cebu, to know if they recovered financially, particularly in recent economic downturns and market forces. After examining the financial data for the years 2022 and 2023 using the identified financial ratios, the authors found that all participating LPG retail stores showed a positive financial performance in terms of their net profit margin, current ratio, debt-to-equity, asset turnover, and cash flow to debt ratios. This implies that LPG retail stores operate efficiently, maintain robust profitability, manage financial obligations correctly, and ensure sufficient liquidity. Additionally, it can give owners a positive perspective on the growth and stability in Talisay City, Cebu.